Problems of Substantive Justice in Criminal Enforcement of Trademark Ownership Disputes - Yanto Jaya; Wagiman Wagiman (Devotion : Journal of Research and Community Service, 2026)
Law as an instrument of justice is essentially created to bring certainty to society with the aim of achieving as much justice as possible. However, the existence of Article 1 number 5 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications—which confirms the first to file principle in the protection of trademark rights holders—actually creates a very essential problem in law, namely justice. The first to file principle, which emphasizes the fulfillment of procedural administrative aspects in providing legal protection for trademark rights holders, actually prevents the application of the principle of substantial justice, which is actually the main element in the protection of intellectual property rights. Normative research—which also raises several case examples such as the DKI Jakarta High Court Decision Number 304/PID/2022/PT.DKI—shows that criminal law enforcement in trademark infringement cases often faces difficulties in proving the element of malicious intent, especially when there is evidence of prior use of the trademark by the defendant or when the validity of the registered trademark is disputed. The results of the study indicate that these conditions create legal uncertainty and demonstrate that the current legal system tends to prioritize procedural justice over substantive justice. This study concludes that the criminal enforcement of trademark infringement in Indonesia requires improvements in legal policy, particularly through clearer regulations regarding the elements of malicious intent and the recognition of prior use of trademarks, so that legal protection can be implemented more fairly and provide greater legal certainty for all parties involved.